Assessment of the inferior mesenteric vein diameter as a surrogate marker to evaluate response to neoadjuvant chemoradiotherapy for locally advanced rectal adenocarcinoma. (1st December 2017) - Ivan, C. V.; Mullineux, J. H.; Verma, R.; Shah, V.; De, A.; Elabassy, M.; Rajesh, A.; Stephenson, J. A.
Abstract: Aim: Neoadjuvant chemoradiotherapy for locally advanced rectal cancer aims to downstage prior to definitive management. Repeat imaging assessment of the tumour post‐therapy has implications for treatment. Our aim was to assess if the inferior mesenteric vein (IMV) diameter measured on CT can be used as a surrogate marker for evaluation of tumour response to neoadjuvant treatment. Method: IMV diameter was assessed in patients with and without locally advanced rectal cancer, pre‐ and post‐radiotherapy, to ascertain if IMV diameter is a surrogate marker of tumour response. Results: IMV diameter was 5.9 mm in patients with rectal cancer vs 4.7 mm in patients without ( P =  0.0001). The baseline IMV diameter was significantly higher for cases with local lymphadenopathy [N0 5.2 mm vs N1/2 6 mm ( P  =   0.0059)] and extramural venous invasion (EMVI) [negative 5.4 mm vs positive 6.4 mm ( P  =   0.0001)]. Post‐radiotherapy there was a significant decrease in the IMV diameter in cases with treatment response compared to non‐responders: the percentage change in IMV diameter was a 17.54% decrease vs 1.39% increase ( P  =   0.0001). These results were reproduced on comparing between magnetic resonance tumour regression grades using ANOVA ( P  =   0.0001). There was also a significant decrease in IMV diameter when assessing lymph node (LN) and EMVI response vs non‐responders ( P  =   0.0001 and 0.0001 respectively). Conclusion: Patients with rectal cancer have a dilated IMV compared with patients without rectal cancer. We confirm that IMV diameter is a potential surrogate marker of LN status and EMVI at baseline. IMV diameter is also a marker of tumour, LN and EMVI response to chemoradiotherapy.